Introduction (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
Introduction to the volume 25 of the journal Palaeohispanica, consisting of the proceedings of the 15th Colloquium of Palaeohispanic Languages and Cultures.